How and when does responsible leadership affect employees’ pro-environmental behavior? - Zhou, Yuanyuan; Ning, Yumei; He, Hui; Li, Dan (Frontiers in Psychology, 2022)
By integrating the resource accumulation perspective and the Job Demands-Resources (JD-R) model, this research explores the impact mechanism of responsible leadership on employees' pro-environmental behaviors (EPB). We conducted a survey to collect data from 319 employees in Chinese companies in three waves. Our research found that responsible leadership had significantly positive effect on EPB; employees’ perceived organizational support toward the environment (POS-E) and green self-efficacy played a serial multiple mediating role; meanwhile, employees' chronic regulatory focus moderated the relationship between responsible leadership and EPB, with promotion focus strengthening the relationship and prevention focus weakening the relationship. Our findings reveal the importance of responsible leadership in shaping EPB, indicate how responsible leaders transform employees' job resources and psychological resources into pro-environmental behaviors, and when the impact of responsible leadership on EPB is stronger. These findings have both theoretical and practical implications.